Sycamore row [compact disc, unabridged] - Grisham, John (Random House, 2013)
The suspense never rests when A Time to Kill's Jake Brigance fights the good fight once again. Often named an all-time favorite by John Grisham's legions of fans, the book that started it all gets a brand-new chapter. America's favorite storyteller returns to Ford County, Mississippi, where defense attorney Jake Brigance will have to fight for justice in a trial that could tear the small town of Clanton apart.